The hidden messengers: cancer associated fibroblasts—derived exosomal miRNAs as key regulators of cancer malignancy - Gou, Zixuan; Li, Jiannan; Liu, Jianming; Yang, Na (Frontiers in Cell and Developmental Biology, 2024)
Cancer-associated fibroblasts (CAFs), a class of stromal cells in the tumor microenvironment (TME), play a key role in controlling cancer cell invasion and metastasis, immune evasion, angiogenesis, and resistance to chemotherapy. CAFs mediate their activities by secreting soluble chemicals, releasing exosomes, and altering the extracellular matrix (ECM). Exosomes contain various biomolecules, such as nucleic acids, lipids, and proteins. microRNA (miRNA), a 22-26 nucleotide non-coding RNA, can regulate the cellular transcription processes. Studies have shown that miRNA-loaded exosomes secreted by CAFs engage in various regulatory communication networks with other TME constituents. This study focused on the roles of CAF-derived exosomal miRNAs in generating cancer malignant characteristics, including immune modulation, tumor growth, migration and invasion, epithelial-mesenchymal transition (EMT), and treatment resistance. This study thoroughly examines miRNA's dual regulatory roles in promoting and suppressing cancer. Thus, changes in the CAF-derived exosomal miRNAs can be used as biomarkers for the diagnosis and prognosis of patients, and their specificity can be used to develop newer therapies. This review also discusses the pressing problems that require immediate attention, aiming to inspire researchers to explore more novel avenues in this field.